Analisis Efektivitas Penggunaan Media Sosial TikTok untuk Pembelajaran Biologi di SMAN 2 Padang - Elsa Nanda Fitrian; Relsas Yogica; Ardi Mustafa (Departement of Mathematics Education, 2023)
This research purpose to determine the effectiveness of using social media TikTok for biology learning at SMAN 2 Padang. This research is a descriptive research with a quantitative approach. Quantitative data were obtained from instrument data in the form of questionnaires with students as respondents. To support this data, interviews were also conducted with biology teachers and direct observation in the school environment. Based on the results of research data processing, it is known that TikTok is quite effective (56.5%) for use in biology learning, this is because TikTok can be used as a medium and source of information for biology learning. Therefore, biology teachers at SMAN 2 Padang may consider using TikTok in biology lessons.